2015
DOI: 10.1108/jfra-04-2014-0023
|View full text |Cite
|
Sign up to set email alerts
|

Financial statement informativeness and intellectual capital disclosure

Abstract: Purpose -The purpose of this paper is to analyse the relationship between financial statement informativeness (FSI) and intellectual capital disclosure (ICD). Design/methodology/approach -While FSI was measured as the explanatory power of financial information in explaining market value, ICD was collected through content analysis of annual reports. A sample of 126 US companies, divided into two groups -high-tech and low-tech companies -were used in this study. Empirical analysis was carried out using the Poiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 66 publications
1
25
0
1
Order By: Relevance
“…Companies that have good intellectual capital will have an impact on high quality work so that they can produce financial report with good integrity. The results of this study also align with the research of [18] and [11], showing that intellectual capital tested simultaneously between VACE, VAHC, and VASC together has a positive effect on the dependent variable, namely the integrity of financial statements.…”
Section: Results Of T-test On Samples Of Indonesian and Malaysian Comsupporting
confidence: 90%
See 1 more Smart Citation
“…Companies that have good intellectual capital will have an impact on high quality work so that they can produce financial report with good integrity. The results of this study also align with the research of [18] and [11], showing that intellectual capital tested simultaneously between VACE, VAHC, and VASC together has a positive effect on the dependent variable, namely the integrity of financial statements.…”
Section: Results Of T-test On Samples Of Indonesian and Malaysian Comsupporting
confidence: 90%
“…Quality intellectual capital will better understand information management so that reports compiled will have more integrity. [18] in their research revealed that Intellectual capital will have a positive influence on the integrity of financial statements. In line with the research conducted by [14] in airlines in Malaysia, intellectual capital can improve the quality of information in the company's financial statements.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…Value creation ini akan mendorong perusahaan untuk melakukan investasi yang cukup besar, sehingga dapat menambah nilai intellectual capital sebuah perusahaan. Maaloul and Zéghal (2015) (Abdoli et al, 2013).…”
Section: Intellectual Capitalunclassified
“…Previous research has established that intellectual capital can be categorised and that the level and the quality of IC disclosure vary across firms and firms from different industries (Maaloul and Zéghal, 2015). The present study differs from the previous studies in terms of the time, data sample, industry type and other contextual factors constructed in the current research paradigm.…”
Section: Discussionmentioning
confidence: 84%